Selective serotonin reuptake inhibitors: New hope in the fight against COVID-19 - Asadi Anar, Mahsa; Foroughi, Elaheh; Sohrabi, Elika; Peiravi, Samira; Tavakoli, Yasaman; Kameli Khouzani, Mozhgan; Behshood, Parisa; Shamshiri, Melika; Faridzadeh, Arezoo; Keylani, Kimia; Langari, Seyedeh Faride; Ansari, Akram; et al. (Frontiers in Pharmacology, 2022)
The emerging COVID-19 pandemic led to a dramatic increase in global mortality and morbidity rates. As in most infections, fatal complications of coronavirus affliction are triggered by an untrammeled host inflammatory response. Cytokine storms created by high levels of interleukin and other cytokines elucidate the pathology of severe covid. In this respect, repurposing drugs that are already available and might exhibit anti-inflammatory effects has received significant attention. With the in-vitro and clinical investigation of several studies on the effect of antidepressants on COVID-19 prognosis, there is suggesting data that Selective Serotonin Reuptake Inhibitors (SSRIs) might be the new hope for early treatment of severely afflicted patients. SSRIs' low cost and availability make them potentially allegeable for COVID-19 repurposing. This review summarizes current achievements and literature about the connection between SSRIs administration and COVID-19 prognosis.